2022
DOI: 10.1002/ptr.7670
|View full text |Cite
|
Sign up to set email alerts
|

Antcin A, a phytosterol regulates SARS‐CoV‐2 spike protein‐mediated metabolic alteration in THP‐1 cells explored by the 1H‐NMR‐based metabolomics approach

Abstract: The mechanism of SARS‐CoV‐2 spike protein‐mediated perturbations of metabolic pathways and modulation of antcin A, a steroid‐like compound isolated from Taiwanofungus camphoratus, are not studied. Here, we investigated the metabolic alteration by SARS‐CoV‐2 spike protein and the regulatory effect of antcin A on SARS‐CoV‐2 spike protein‐induced metabolic changes in the Phorbol 12‐myristate 13‐acetate (PMA)‐induced human monocytes (THP‐1) using proton nuclear magnetic resonance (1H‐NMR) and MetaboAnalyst 5.0 sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Our recent studies have shown that antcins, citronellol, and limonene significantly reduce the expression of ACE2 receptors, facilitating the entry of SARS-CoV-2 into cells 19 . Furthermore, antcin-A regulates metabolomic pathways altered by the SARS-CoV-2 spike protein in the THP-1 cells, as observed through 1 H-NMR metabolomic analysis 20 . These findings suggest that antcins can potentially develop therapeutic drugs against COVID-19.…”
Section: Introductionmentioning
confidence: 84%
“…Our recent studies have shown that antcins, citronellol, and limonene significantly reduce the expression of ACE2 receptors, facilitating the entry of SARS-CoV-2 into cells 19 . Furthermore, antcin-A regulates metabolomic pathways altered by the SARS-CoV-2 spike protein in the THP-1 cells, as observed through 1 H-NMR metabolomic analysis 20 . These findings suggest that antcins can potentially develop therapeutic drugs against COVID-19.…”
Section: Introductionmentioning
confidence: 84%